2005
DOI: 10.1161/01.res.0000182903.16652.d7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial/Pericyte Interactions

Abstract: Abstract-Interactions between endothelial cells and mural cells (pericytes and vascular smooth muscle cells) in the bloodvessel wall have recently come into focus as central processes in the regulation of vascular formation, stabilization, remodeling, and function. Failure of the interactions between the 2 cell types, as seen in numerous genetic mouse models, results in severe and often lethal cardiovascular defects. Abnormal interactions between the 2 cell types are also implicated in a number of human pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
1,668
1
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,788 publications
(1,714 citation statements)
references
References 134 publications
31
1,668
1
14
Order By: Relevance
“…27 Interestingly, in TPA-treated skin tissues, ␣-SMA ϩ cells are mainly located around the blood vessels in the skin ( Figure 1C and see Supplemental Figure S2, http://ajp.amjpathol.org) and these cells are likely to be vascular smooth muscle cells or pericytes around the vascular walls. 28 We double-stained the skin tissue with ␣-SMA and FSP1 and found that there were seldom ␣-SMA and FSP1 double positive cells in the TPA-treated skin ( Figure 1B), which is similar with the former discovery in the tumor, 29 indicating that TPA mainly simulated the proliferation of a unique population of FSP1 ϩ fibroblasts that are regarded as the most important class of fibroblasts present in many tissues. 20,30 FSP1 usually serves as a sensitive and specific marker for fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
“…27 Interestingly, in TPA-treated skin tissues, ␣-SMA ϩ cells are mainly located around the blood vessels in the skin ( Figure 1C and see Supplemental Figure S2, http://ajp.amjpathol.org) and these cells are likely to be vascular smooth muscle cells or pericytes around the vascular walls. 28 We double-stained the skin tissue with ␣-SMA and FSP1 and found that there were seldom ␣-SMA and FSP1 double positive cells in the TPA-treated skin ( Figure 1B), which is similar with the former discovery in the tumor, 29 indicating that TPA mainly simulated the proliferation of a unique population of FSP1 ϩ fibroblasts that are regarded as the most important class of fibroblasts present in many tissues. 20,30 FSP1 usually serves as a sensitive and specific marker for fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
“…2,3,6,9,10,12e16 Such broad adaptability is proposed to enable pericytes and resident fibroblasts to repeatedly adjust to support growing, injured, or regenerating vascular or airway structures. 2,6,13 Figure 1 Tissue architecture and mesenchymal lineages in the lung. A: Electron microscopy photomicrographs of normal mouse lung showing fibroblast processes abutting epithelium and pericyte processes attached to endothelium and within a loose capillary basement membrane.…”
Section: Characteristics Of Lung Pericytes and Resident Fibroblastsmentioning
confidence: 99%
“…Reciprocal communication between endothelial cells and pericytes also involve angiopoietin-Tie2 signaling that is required for vessel stabilization (Armulik et al, 2005). Paracrine signaling between pericytes and endothelial cells is suggested by the general expression of the Tie2 receptor on endothelial (Sato et al, 1995) cells, whilst its ligand Ang1 is mainly expressed on juxtaposed perivascular pericytes (Sundberg et al, 2002).…”
Section: Pericyte/vsm-endothelial Cell Interactions In the Tumor Micrmentioning
confidence: 99%